Operator Duals of Vector Sequence Spaces - A. Ansari2, K. B. Gupta1*; Ashfaque (Recent Research in Science and Technology, 2011)
T. Balasubramaniam and A. Pandiarani [1] have defined the sequence spaces G(x). l (x), G(x) and have studied some topological property of their Köthe-Toeplitz duals in operator form. In this paper we define the new sequence spaces G0(x, p), Ge(x, p) and G¥(x,p) and have studied some topological property of their Köthe-Toeplitz duals in operator form.